The Challenge of Diagnosing and Managing Pulmonary Arterial Hypertension in Systemic Sclerosis with Interstitial Lung Disease - Elisabetta Zanatta; Martina Perazzolo Marra; Giulia Famoso; Elisabetta Balestro; Chiara Giraudo; Fiorella Calabrese; Federico Rea; Andrea Doria (MDPI AG, 2022)
Pulmonary hypertension (PH) in patients with Systemic Sclerosis (SSc) may stem from a variety of underlying causes, thus making a correct diagnosis and management difficult. The main challenges lie in the distinction between pulmonary arterial hypertension (PAH, group 1) and PH due to interstitial lung disease (PH-ILD, group 3) in patients with concomitant lung fibrosis - a very common occurrence in SSc. A consensus among experts remains elusive. Some studies have suggested that among SSc patients with PH, those with an ILD extension > 20% at high-resolution computed tomography (HRCT) should be considered as affected by PH-ILD, whereas other Authors have found that a wide proportion of these patients exhibit features of both PAH and group 3 PH-ILD. We report the case of a 46-year-old male SSc patient with a stable and extensive ILD (>20%) who developed a histologically documented pulmonary vasculopathy typical of PAH and received PAH-specific treatment as bridge to transplant. Moreover, we documented PH disease course by right heart catheterization (RHC), with and without specific vasodilator therapies, which are essential in PAH but not indicated and/or harmful in PH-ILD.